2014
DOI: 10.3390/rs6087469
|View full text |Cite
|
Sign up to set email alerts
|

Soil Surface Sealing Effect on Soil Moisture at a Semiarid Hillslope: Implications for Remote Sensing Estimation

Abstract: Robust estimation of soil moisture using microwave remote sensing depends on extensive ground sampling for calibration and validation of the data. Soil surface sealing is a frequent phenomenon in dry environments. It modulates soil moisture close to the soil surface and, thus, has the potential to affect the retrieval of soil moisture from microwave remote sensing and the validation of these data based on ground observations. We addressed this issue using a physically-based modeling approach that accounts expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…The dynamics of the water regime in sealed and unsealed soil profiles is highly depending upon the intensity of the rainfall events and their temporal distribution throughout the season [ Assouline et al ., ; Sela et al ., ]. Soil water availability, and consequently, VWU, depends on several factors as the initial soil water content prior to the rainfall event, the rainfall event intensity, and the length of the drying interval until the subsequent event.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dynamics of the water regime in sealed and unsealed soil profiles is highly depending upon the intensity of the rainfall events and their temporal distribution throughout the season [ Assouline et al ., ; Sela et al ., ]. Soil water availability, and consequently, VWU, depends on several factors as the initial soil water content prior to the rainfall event, the rainfall event intensity, and the length of the drying interval until the subsequent event.…”
Section: Resultsmentioning
confidence: 99%
“…The ''gradient'' BC potentially enables the lateral movement of subsurface fluxes through the sides of the transect, which in our case were not observed due to the absence of slope inclination. Similar to previous modeling studies at the Lahav area [Sela et al, 2012[Sela et al, , 2014[Sela et al, , 2015, the bottom BC was set to free drainage as the subsurface bedrock at the study site was found to be frequently fractured [Bahat, 1987;Howard and Bahat, 2005] and presented highly variable preferential drainage [Dahan et al, 1999]. The top BC requires rainfall and potential evapotranspiration (PET) rates as input.…”
Section: The Modelmentioning
confidence: 95%
“…These findings are significant from a management perspective to understand linkages to how GI is designed, built, and managed. Despite the recognized importance of soil moisture as a state variable underlying many ecosystem services, only a few researchers (e.g., Sela, Svoray, & Assouline, ) provide insights regarding soil moisture and soil crust layer. Additional research would ideally include field studies to test the role of actual vegetation canopies on infiltration, recharge, and runoff processes.Modeling could also help to better understand the potential role that soil crusts may play in limiting the ability of engineered GI systems, and other managed urban green spaces to attenuate stormwater, reduce flood frequency, replenish soil moisture, promote groundwater recharge, and provide other crucial ecosystem services, particularly in the context of projected changes in the amount and timing of precipitation in the context of climate change.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are significant from a management perspective to understand linkages to how GI is designed, built, and managed. Despite the recognized importance of soil moisture as a state variable underlying many ecosystem services, only a few researchers (e.g.,Sela, Svoray, & Assouline, 2014) provide insights regarding soil moisture and soil crust layer. Additional research would ideally include field studies to test the role of actual vegetation canopies on infiltration, recharge, and runoff processes.…”
mentioning
confidence: 99%
“…Most agricultural soils, especially in arid and semi-arid regions, suffer from some physical and chemical problems, such as salinization, alkalinity, structure deterioration, low aggregations and low organic matter content (Sela et al, 2014 andAcir andGunal, 2020), and to reduce these problems or reduce their negative effects on soil and agricultural production (Pires et al, 2017). Many researchers in the field of soil management and conservation (Agassi et al, 1985, Pagliai et al, 2000b, Sela et al, 2012and Pires et al, 2017 recommended that more experiments and research be conducted in order to improve the properties of degraded soils that suffer from some problems and constraints that affect their productivity to obtain the best economic return.…”
Section: ‫الــرافـديــن‬ ‫زراعـــة‬ ‫مـجـلـــة‬mentioning
confidence: 99%